1991
DOI: 10.1287/ijoc.3.4.376
|View full text |Cite
|
Sign up to set email alerts
|

TSPLIB—A Traveling Salesman Problem Library

Abstract: This paper contains the description of a traveling salesman problem library (TSPLIB) which is meant to provide researchers with a broad set of test problems from various sources and with various properties. For every problem a short description is given along with known lower and upper bounds. Several references to computational tests on some of the problems are given. INFORMS Journal on Computing, ISSN 1091-9856, was published as ORSA Journal on Computing from 1989 to 1995 under ISSN 0899-1499.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1,090
0
43

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,189 publications
(1,214 citation statements)
references
References 0 publications
4
1,090
0
43
Order By: Relevance
“…Since there are no open-source benchmarks for testing the algorithms of the MTSP, we computed some instances presented in TSPLIB [30], which is the standard public library for the TSP. Although the MTSP is different to the TSP, typical instances and optimal results of these can reflect the performance of MDCP to a great extent.…”
Section: Experiments and Computational Resultsmentioning
confidence: 99%
“…Since there are no open-source benchmarks for testing the algorithms of the MTSP, we computed some instances presented in TSPLIB [30], which is the standard public library for the TSP. Although the MTSP is different to the TSP, typical instances and optimal results of these can reflect the performance of MDCP to a great extent.…”
Section: Experiments and Computational Resultsmentioning
confidence: 99%
“…The algorithm runs on a Pentium 1Ghz, 256 MB RAM, and uses CPLEX 6.5 as LP solver. The two sets of test instances are taken from the TSPLIB [23] and Ascheuer's asymmetric TSPTW problem instances [1]. Table 4 shows the results for small TSP instances.…”
Section: Computational Resultsmentioning
confidence: 99%
“…In Tables 2 and 3 we report the quality of the heuristic with respect to the ratio. The TSP instances are taken from TSPLIB [23] and the asymmetric TSPTW instances are due to Ascheuer [1]. All subproblems are solved to optimality with a fixed strategy, as to make a fair comparison.…”
Section: Quality Of Heuristicmentioning
confidence: 99%
“…The Held-Karp Lower Bound (HKLB) is calculated by using a 1-tree with modified edge weights. Johnson et al showed in [31] that for randomly generated instances the optimal tour length is on average less than 0.8% above the Held-Karp bound and for most instances from the TSPLIB [40] collection less than 2%. So, the Held-Karp bound can be used as an evaluation criterion for TSP instances where no optimal solution is known.…”
Section: Algorithmsmentioning
confidence: 99%
“…• From Reinelt's TSPLIB [40] the following instances were taken: fl1577, fl3795 (both clustered instances), pr2392, pcb3038 (both drilling problems), fnl4461 (map of East Germany), usa13509 (map of the United States), pla33810 and pla85900 (both programmed logic array). The number in the instance names denotes the number of cities in the instances.…”
Section: Testbedmentioning
confidence: 99%